Analisis Authentic Happiness Dewasa Awal Berdasarkan Jenis Kelamin - Syahda, Mutiara; Nofriza, Fatma (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2025)
Happiness in important aspect for individual psychological well-being, especially in early adult individuals who are characterized by various life transitions such as identity, self-adjustment in the workplace and forming social relationships. However, the experience of happiness that occurs in individuals is different between men and women, that is because the social role and the pressure that occurs are often different. This research focuses on the approach of happiness according to Seligman, namely authentic happiness. The purpose of this research is to analyze the authentic happiness of early adults based on gender in Lenteng Agung Village. This research uses a quantitative approach with a comparative method. This study used the cluster sampling method with the number of respondents as many as 54 early adults. Unlike other measures of happiness, Authentic Happiness Inventory (AHI) tends to measure current levels of happiness and assess changes in happiness based on a meaningful life and having goals, pleasure and positive emotions, involvement in life activities and interpersonal connections. From the results of the study, the significance value of 0,027 means that there is a difference in early adult authentic happiness based on gender in Lenteng Agung Village. Thus, this research can contribute to psychological literature that emphasizes the importance of authentic happiness towards gender factors and can be used as a basic material in improving the emotional well-being of early adults in various social and cultural contexts.